Rural‐urban differences in uptake of diabetes self‐management education among Medicare beneficiaries: Results from the 2016 to 2018 Medicare Current Beneficiary Survey - Luo, Huabin; Basu, Rashmita; Bell, Ronny A.; Rafferty, Ann P.; Zeng, Xiaoming; Qu, Haiyan; Dove, Cameron (The Journal of rural health, 2022)
Purpose To assess rural‐urban differences in participation rates of diabetes self‐management education and associated factors among Medicare beneficiaries with type 2 diabetes (T2DM). Methods Data were from the 2016 to 2018 Medicare Current Beneficiary Survey (MCBS). Participation in diabetes self‐management education was self‐reported. The study sample included 3,799 beneficiaries aged 65 years and older with self‐reported T2DM. Logistic regression was used to assess the association of participation in diabetes self‐management education and residential location. Sampling weights embedded in the MCBS were incorporated into all analyses. Findings Overall, the participation rate of diabetes self‐management education was 46.8% (95% CI: 44.4%‐49.2%). The rate was 40.3% for beneficiaries in rural areas, 48.0% for suburban areas, and 47.3% for urban areas. About 31% of beneficiaries newly diagnosed with diabetes did not participate within the past year. Controlling for other covariates, beneficiaries in rural areas were less likely to have participated in diabetes self‐management education (AOR = 0.73, 95% CI: 0.55‐0.95) than those living in urban areas. Asian Americans were less likely to have participated (AOR = 0.49, 95% CI: 0.28‐0.84) than Whites. Those who were older, with lower education, and lower income levels were less likely to have participated (P < .05). Conclusions Recent MCBS data indicate that more than half of Medicare beneficiaries with T2DM did not participate in diabetes self‐management education, and the participation rate in rural areas was 7 percentage points lower than that ​in urban areas. The study findings highlight challenges to maximize the benefits of participating in diabetes self‐management education, particularly in rural areas.